Kimia klinik ANALISIS QUALITY CONTROL KADAR HEMOGLOBIN DAN ERITROSIT BERDASARKAN WESTGARD: QUALITY CONTROL ERITROSIT DAN HEMOGLOBIN - aini; Bhakti Ananda Solikhah; Pauzan; Ika Nurfajria Mentari (LPPM Universitas Abdurrab, 2025)
A clinical laboratory is a place to conduct and serve health examinations. One of these is a hematology examination using a hematology analyzer. Quality control is an activity carried out to ensure internal quality within the laboratory. This research method applies a quantitative descriptive approach. This study was conducted at the Kimia Farma Clinic in Mataram City, from August to October 2024. The examination results were obtained from quality control of white blood cell and hemoglobin counts using a Sysmex KX-21 Hematology Analyzer. The results of this study indicate that the erythrocyte and hemoglobin examinations obtained fairly good measurement accuracy, but the mean value of the hemoglobin examination from August to October had a small difference compared to the actual value. The coefficient of variation (CV%) at low, normal, and high levels tended to beabove the maximum limit of CV <8%. According to the results of this Westgard examination rule, the evaluation of the Levey-Jennings chart showed that control data at certain levels were affected by the 12s rule as a warning rule as well as the 22s rule and R4s rule of rejection. The conclusion is that the erythrocyte and hemoglobin level examinations have quite good measurement accuracy because the quality control results are mostly within the control range. Precision is affected by recurring random errors, which need to be addressed to maintain consistency of results. The total error frequency is three random errors (once every month: August, September, October) and three systematic errors (once every month: August, September, October).